DESCRIPTION OF LOCAL POTENTIALS IN COMMUNITY ECONOMIC EMPOWERMENT IN THEVILLAGE OF GISTINGATAS, DISTRICTS GISTING, TANGGAMUS - Anita Lisdiana; Wellfarina Hamer; Supardi Supardi; Siti Mariya Ulfa (Nizham Jurnal Studi Keislaman, 2019)
Local potential is the ability or power possessed by an area or areas that can be developed to produce a benefit or advantage for the region. Utilization of local potential carried by villagers Gisting Atas, is utilization of water resources for clean water source, manufacture of fish ponds, watering plants and manufacture of turbine (power generation from water) in realizing the community's ability to meet their needs.This research is a kind of field research and this research is classified as descriptive research. Data collection method I use is the interview method as the principal method, while the method of observation and documentation as complementary method. The analysis used by the authors is a qualitative analysis conclusion using inductive way of thinking. The findings of this study note that the utilization of water resources in the economic empowerment of the people in the village of Gisting Atas, District Gisting, Tanggamus, not fully utilized, the lack of public participation in the utilization of the local potential, so that the local potential is only used by a particular community. Thus, it can be concluded that the utilization of water resources in the village of Gisting Atas, not fully utilized and have not been well managed by the local community, thus not providing optimal economic impact, while the contribution of water resources in the economicenhancement in the village of Gisting Atas is not looks significantly, but enough to meet the daily needs of the community.